Program Transformasi Teknologi Peternakan Cerdas: Optimalisasi Monitoring Bibit Kambing Unggul Berbasis IoT dan Integrasi Circular Economy melalui Pupuk Organik - Ariq Cahya Wardhana; Arif Amrulloh; Wahyu Andi Saputra; Famila Dwi Winati; Mochammad Edrick Firjatullah; Adhimas Arya Saputra; Farrel I’zaz Yuwono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This study presents the implementation of a Smart Livestock Technology Transformation Program designed to improve the efficiency and sustainability of smallholder goat farming through the integration of Internet of Things (IoT) monitoring systems and circular economy practices. The initiative was motivated by the limited accuracy of conventional manual measurements, the absence of continuous growth monitoring, and the underutilization of goat manure as a valuable agricultural resource. This research aims to develop an IoT-based monitoring system capable of automatically recording goat body weight and growth performance, while simultaneously transforming livestock waste into organic fertilizer with economic benefits for local farmer groups. The methodology adopts a participatory action research and research and development approach, involving system design, device installation, digital literacy training, organic fertilizer processing, and performance evaluation. The results demonstrate that the IoT system significantly improves measurement accuracy, increases monitoring frequency, reduces human error, and enhances early detection of growth anomalies. The manure processing activities, supported by mixing and grinding machines, produce high-quality organic fertilizer with better homogeneity and ease of application. The integration of IoT and circular economy practices yields positive impacts including increased livestock productivity, improved digital capabilities among farmers, reduced environmental waste, and the creation of new economic value within the community. The findings indicate that this integrated model has strong potential for broader replication in other small-scale livestock communities facing similar challenges.